The Effect of Ratio of Tempeh Puree With Sweet Corn Puree and Stabilizer Ratio on The Quality of Jam - Fitri Riyanti; Herla Rusmarilin; Rona J Nainggolan (Universitas Sumatera Utara, 2014)
The research was conducted to determine the effect of tempeh puree with sweet corn puree and ratio of stabilizers suitable to produce the quality and organoleptic of jam. The reseach had been performed using factorial completely randomized design (CRD), with two factors i.e : ratio of tempeh porridge with sweet corn porridge (T) : (80% : 20%, 60% : 40%, 40% : 60%, 20% : 40%) and ratio of carboxy methyl cellulose (CMC) and Arabic gum (P) : (1% : 0%, 0,75% : 0,25%, 0,25% : 0,75%, 0% : 1%). The parameters analyzed were moisture, ash , protein, fat, and fiber content, total soluble solid, total microbes, score of color, aroma and taste, score of stickiness and organoleptic values (colour, flavor, and taste). The resuls showed that the ratio of of tempeh puree with sweet corn puree had highly significant effect on moisture, ash, fat, protein, and fiber content, total soluble solid, score of color, flavor and taste, stickiness and organoleptic values (colour, flavor, and taste). The ratio of carboxy methyl cellulose (CMC) and Arabic gum had highly significant effect on moisture, fiber, fat, and protein content, total soluble solid, total microbes, and score of stickiness. The interaction of the two factors had significant effect on fat content. The ratio of tempeh puree with sweet corn puree 80% : 20 % and ratio of carboxy methyl cellulose (CMC) and Arabic gum 1% : 0 % produced the best quality of jam. Keywords : Arabic gum, carboxy methyl cellulose, jam, sweet corn , tempe